Monitoring training load in young professional soccer players - Los Arcos, A.; Gil-Rey, E.; Izcue, I.; Yanci, J. (AGON International Journal of Sport Sciences, 2013)
The aims of this study were to find the correlation between Edwards' heart rate (HR) based training load (TL) and session rate of perceived effort (sRPE) TL methods,to quantify and compare the weekly TL using the same weekly training pattern, and compare the TL among the common types of training used in soccer. 19 young professional male soccer players (age=20.95±1.66 yr,height=1.81± 0.63m, bodymass=76.10±7.75kg ) from the 2 nd B championship division of the Spanish Liga, participated in this study. A significant correlation (p<0.001 ) was found Between Edwards' HR--based and two (respiratory= 0.88±0.06 and muscular=0.84±0.07) RPE--based TL methods. Significant differences in weekly and training type's mean teams RPEres--TL and sRPEmus-TL were also found. Knowledge of the TL is important in team sports to Be able to adjust the organization of training sessions